Aziridination of 11-pregnene-3,20-dione using PhI=N-Ses - Di Chenna, Pablo Hector (2000)
The copper-catalyzed reaction of [N-(Ses)imino]phenyliodinane with 11-pregnene-3,20-dione gave the corresponding aziridine in 53% yield. The Ses protecting group could be conveniently removed using the TASF reagent. Furthermore, nucleophilic ring opening of the protected N-Ses-aziridine with thiophenol in the presence of a Lewis acid led to introduction of the thiophenol group at the α-12 position but, unexpectedly, concomitant loss of the Ses group to provide compound 10.